ESTUDO “IN LOCO” DA CONTRAÇÃO DE POLIMERIZAÇÃO E DO GRAU DE CONVERSÃO DE CIMENTOS RESINOSOS UTILIZADOS NA FIXAÇÃO DE PINOS INTRARRADICULARES - Mora, Camilo Andrés Pulido (2014)
The aim of this study was to investigate the shrinkage-strainand degree of conversion inside the rootcanal"in situ"of resin cements used to lute fiber posts (Whitepost DC, FG). Thirty maxillary canines with similar root length average were selected (14 mm ± 1 mm). Each root canal was treated with crown-down technique and filled with gutta-percha, leaving 4 mm of apical seal.One week later, the roots were prepared following fiber post system manufacturer’s instructions. For the cementation, teeth were randomly divided into 2 groups (n = 15) according to the resin cement used: Group 1: dual-cured resin cement RelyX™ ARC – Adper Scotchbond™ Multipurpose Plus Adhesive (3M/ESPE) and Group 2: dual-cured resin cement RelyX™ U200 (3M/ESPE). Two fiber optic sensors with recorded Bragg gratings were attached to the coronal section (not in contact with the root) of each post before inserting the resin cement inside the root canal. These sensors measured the deformations of the cement over the coronal and apical section of the root (μe). Once measured, the specimens were sectionated in order to obtain slides on its cervical and apical sections. The degree of conversion of the cements on each third was analyzed by μ-Raman micro-spectroscopy. The data were statitsticallyanalyzed by two-way ANOVA (p = 0.05). The dual-curedconventional resin cement tested in this study showed the highest values of shrinkage-strain and degree of conversion; cervical region showed higher values than apical region in both of resin cements.